Investigating and operationalising the mindful organising construct in an Air Traffic Control organisation. (December 2019) - Callari, Tiziana C.; McDonald, Nick; Kirwan, Barry; Cartmale, Keith
Highlights: An operational conceptualisation of mindful organising is grounded in a case-study of Air Traffic Control. 'Coordination between groups' and 'Accountability' emerge as critical additional dimensions for mindful organising. This starts to specify the organisational conditions for enacting a 'collective mind'. Abstract: Mindful organising highlights the commitment to recognise latent failures, deviances, and surprises that may foreshadow the development of larger unwanted events. This social process is fed by extensive real-time communication and interaction by front-line operators. Safety is therefore achieved through these human processes and relationships. But what should an organisation do in practice to be mindful? We explored this in the Maastricht Upper Area Control Centre (MUAC), an Air Traffic Control (ATC) organisation, which has reported for many years high-standards of safety (i.e. very low numbers of serious incidents). A single-case study approach was used to support the in-depth description and understanding of the phenomenon within its real-life context. The mindful organising principles have been followed to design the protocol for data collection and its multiple sources of information (semi-structured interviews, observations, workshop, documents, analysis of the current tools in use). Data triangulation and the use of a software for Qualitative Data Analysis (QDA) have supported the achievement of data reliability and validity. The results provide a picture of the current safety mindful organising in place, assessing the way safety procedures and processes are advanced, the extent to which weak signals are detected, recorded, and analysed, how the best practices/recommendations are implemented, and the overall quality of the information flow. The results of this study suggest improvements in the mindful organising construct from an organisational point of view. This paves the way for the definition of requirements to advance a model able to provide clearer guidance to any organisation wishing to sustain mindful organising.